1997
DOI: 10.1016/s0092-8674(00)80217-2
|View full text |Cite
|
Sign up to set email alerts
|

Repression by Ume6 Involves Recruitment of a Complex Containing Sin3 Corepressor and Rpd3 Histone Deacetylase to Target Promoters

Abstract: Sin3 and Rpd3 negatively regulate a diverse set of yeast genes. A mouse Sin3-related protein is a transcriptional corepressor, and a human Rpd3 homolog is a histone deacetylase. Here, we show that Sin3 and Rpd3 are specifically required for transcriptional repression by Ume6, a DNA-binding protein that regulates genes involved in meiosis. A short region of Ume6 is sufficient to repress transcription, and this repression domain mediates a two-hybrid and physical interaction with Sin3. Coimmunoprecipitation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
469
2
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 513 publications
(510 citation statements)
references
References 34 publications
32
469
2
4
Order By: Relevance
“…Ume6 exerts control of transcription by forming a complex with the corepressor Sin3 and the histone deacetylase Rpd3 (15). Accordingly, we extended our analysis by examining the level of Atg8 in rpd3Δ and sin3Δ strains.…”
Section: Resultsmentioning
confidence: 94%
“…Ume6 exerts control of transcription by forming a complex with the corepressor Sin3 and the histone deacetylase Rpd3 (15). Accordingly, we extended our analysis by examining the level of Atg8 in rpd3Δ and sin3Δ strains.…”
Section: Resultsmentioning
confidence: 94%
“…Previous work has shown that these factors interact with other proteins to form a heterogeneous multiprotein complex of Ͼ1 MDa that is recruited to the promoters of target genes by the DNA-binding protein Ume6p (26)(27)(28). The deacetylase activity of Rpd3p then results in the formation of a localized domain of hypoacetylated chromatin that is thought to inhibit transcription by preventing the recruitment of the transcriptional machinery (29)(30)(31)(32). Significantly, genomewide localization studies have revealed that, apart from residing on the promoter regions of its target genes, the Sin3p͞Rpd3p complex also binds to nonpromoter sequences independently of Ume6p.…”
mentioning
confidence: 99%
“…Based on the ideas about the function of the SNF/SWI complex, the simplest model for explaining the defect of nps1-105 in meiotic gene activation is that Nps1p is required for recruiting the Ime1p-Ume6p complex on URS1 sites or in converting a negative regulatory complex formed on the URS1 site through Ume6p to a positive Ime1p-Ume6p complex. Recent studies by Kadosh & Struhl (1997) and Kasten et al (1997) have shown that Ume6p forms a huge complex with Sin3p, Rpd3p and possibly with some other proteins when it functions as a repressor. The starvation of a/␣ cells stimulates IME1 expression and Ime1p then converts Ume6p to activator with Rim11p, while the mechanism of this conversion is unclear.…”
Section: Discussionmentioning
confidence: 99%